An analysis on the economic development and deforestation - E.S. Siregar; S.U. Sentosa; A. Satrianto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aimed to investigate endogenous variables namely, economic development and deforestation, in North Sumatra, and examine their determinants. Both variables are substantial in a country community welfare with harmonized environmental sustainability as a legacy for future generations.METHODS: In this quantitative study, secondary data in the form of time series data from 1991 to 2020 with a total of 30 years were analyzed. The novelty of this study is its aim to combine deforestation variables and their determinants in a research model related to economic development. In this study, the determinants of economic development used were education, health, mineral resources and forest resource, whereas those of deforestation, were  forest resource,  institutional factors, population density, and economic development.FINDINGS: The data analysis revealed that the economic development in North Sumatra was significantly influenced by education, health, and mineral resources, excluding forest resources. Simultaneously, the determinants influenced economic development by 74.15 percent. Education contributed 27 percent, health 71 percent, mineral resources 12 percent and forest resources 29 percent to economic development. Forest resources and institutions had a significant influence on deforestation in North Sumatra, whereas population density and economic development did not have a significant effect. Simultaneously, the determinants influenced deforestation by 77.24 percent. Partial, forest resources and institutions were identified and significant effect but population density does not significantly affect it. Forest resources contributed 14 percent to deforestation, institutional factors 72 persent, population density 3 percent and economic development 57 percent.CONCLUSION: The findings of this study, indicated that education and health have a major effect on economic development whereas forest resources do not however, forest resources significantly affect deforestation. This means that an increasing environmental damage  removes forest cover. Thus, it is recommended that the government increase human resource in terms of education and health, which are  essential in prioritizing human resource development as a fundamental factor. It is also important to set the limit to long-term natural resource exploitation, consider environmental damages, and improve institutional quality. The government needs to explore alternative sources that are more sustainable and environmentally friendly, such as ecotourism, and renewable energy. Renewable energy can be a reliable source of energy that will help reduce reliance on fossil fuels while also minimizing environmental impacts.